Framtidens krav på containerhantering - Med inriktning på hamninfrastruktur i containerterminaler med fokus på Göteborgs hamn - Halldén, Sebastian; Lövberg, Joakim (My University, 2016)
The Container industry is growing. Ships are built to carry an increasingly amount of containers, and there is no limit to how much a ship will be carrying in the future in sight. What are the reasons for delays at container port terminals? Are there any theoretical calculations that show when delays begin at container terminals due to defects in container handling? These are some of the questions that will be answered in this thesis. The port of Gothenburg will be the port we have chosen to focus on in this thesis. Many of the infrastructural parts that the container terminal in the port of Gothenburg will be upgrading, is going to be used as examples of how ports plan to meet the qualifications of effective container handling in the future. We have used a general plan and an interview from the port of Gothenburg to find information about the plans they have for the future of the container terminal, and we have used literature found at Chalmers University to find theoretical information about delays at container terminals. Our results as we have expected them to be. The reasons for delays that appear to be different for each infrastructural part of a container terminal cannot be precise. Especially due to the fact that it is being compared to a specific port that has different infrastructural properties than the port used in the theoretical equation. The result does although show that disregarding the fact that the results cannot be precise, they can still be compared and parallels can be drawn showing the reasons behind the delays. This thesis will discuss the infrastructure of a container terminal, and how container terminals prepare to meet the future qualifications of container handle.
Keywords: Transport; Transportteknik och logistik; Transport; Transport Systems and Logistics